Preparation of Templated Materials and Their Application to Typical Pollutants in Wastewater: A Review - Li, Hanbing; Wang, Li; Wei, Yifei; Yan, Wei; Feng, Jiangtao (Frontiers in Chemistry, 2022)
As the pollution and destruction of global water resources become more and more severe, the treatment of wastewater has attracted significant attention. The template method is a synthetic method in which the template is the main configuration to control, influence and modify the morphology and control the dimensions of the material, thus achieving the properties that determine the material. It is simple, highly reproducible and predictable, and more importantly, it can effectively control the pore structure, size and morphology of the material, providing a novel platform for the preparation of adsorbent materials with excellent adsorption properties. This review focuses on the classification of the templates according to their properties and spatial domain-limiting capabilities, reviews the types of hard and soft template materials and their synthetic routes, and further discusses the modulation of the morphological structure of the materials by the introduction of templates. In addition, the application and adsorption mechanisms of heavy metal ions and dyes are reviewed based on the regulatory behavior of the template method.